2016
DOI: 10.1063/1.4939547
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative contrast-enhanced optical coherence tomography

Abstract: We have developed a model to accurately quantify the signals produced by exogenous scattering agents used for contrast-enhanced Optical Coherence Tomography (OCT). This model predicts distinct concentration-dependent signal trends that arise from the underlying physics of OCT detection. Accordingly, we show that real scattering particles can be described as simplified ideal scatterers with modified scattering intensity and concentration. The relation between OCT signal and particle concentration is approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 25 publications
4
25
0
1
Order By: Relevance
“…However, strong OCT signals of GNPRs were imaged in whole blood at concentrations ≥250 pM. We showed that the OCT signal of GNPRs in blood increased with concentration, and the experimental data matched well with the prediction of our physical model 26 (Figure 1d). We calculated the detection limit of GNPRs in blood to be 206 pM at a signal-to-noise ratio of 3.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…However, strong OCT signals of GNPRs were imaged in whole blood at concentrations ≥250 pM. We showed that the OCT signal of GNPRs in blood increased with concentration, and the experimental data matched well with the prediction of our physical model 26 (Figure 1d). We calculated the detection limit of GNPRs in blood to be 206 pM at a signal-to-noise ratio of 3.…”
supporting
confidence: 81%
“…However, the increase of OCT amplitude with each injection was not significant for GNPR concentrations in blood ≥0.75 nM, which can be explained by a multi-scattering effect according to our physical model. 26 Next we investigated OCT angiograms of healthy mouse ears (Figure 3a-c) with increasing concentrations of GNPRs. We obtained the OCT angiograms by detecting the blood vessels with NSV followed by segmenting the vessels with a hybrid intensity/shape-based compounding algorithm.…”
mentioning
confidence: 99%
“…For simplicity, we do not take into the consideration of the DC, mutual cross-correlation, and noise components in the OCT signal formulation because they are not relevant to our discussion. The OCT signal can be described as the superposition of all the light fields reflected from the scatters within an imaging voxel (coherent volume) in the medium [21]. Because the light field is treated as a vector of magnitude and angle (phasor) that are time-variant due to a random arrangement of the scattering particles within the imaging voxel, the OCT signal can be expressed as a sum of many random phasors as…”
Section: Analytical Model Of Omag Signalmentioning
confidence: 99%
“…According to Winertraub et al [21], with the simplified assumptions: 1) single scattering regime, 2) reflections modeled by ray optics and 3) all particles having the same reflectance in the imaging voxel, the OCT signal detected from the scattering particle is proportional to a square root of the number of particles (N) within the imaging voxel that is given by [21] …”
Section: Analytical Model Of Omag Signalmentioning
confidence: 99%
“…The advantages of LSPR make Cu-Sn-S nanocrystals can serve as a contrast-enhanced molecular imaging for cancer detection in clinical setting. Such as Optical Coherence Tomography (OCT), [28][29][30][31][32] magnetic resonance imaging (MRI) and positron emission tomography (PET). As we know, there are many researches have reported the synthesis and characterization of Cu-Sn-S nanocrystals.…”
Section: Introductionmentioning
confidence: 99%